The multicultural social fabric and its impact on the assimilation of the French and British education systems in Cameroon - Mekhanet, Fatima Zohra Gueddouda (Universitas Negeri Malang, 2025)
This article examines the impact of Cameroon's diverse social fabric on the successful adoption of the French and British colonial educational systems. Relying on the descriptive analytical approach, the historical and social contexts that contributed to local communities’ acceptance of colonial education were studied, with a focus on cultural values, ethnic, and religious diversity. The research aims to provide a comprehensive view on how education and educational policies are affected by cultural and social diversity in Cameroon. The research began with a historical background on ethnic and cultural diversity in pre-colonial Cameroon, pointing to the nature of the diverse social fabric and its role in shaping societies’ response to new changes. The article then described the French and British educational systems, focusing on the ideological differences between French centralization and British decentralization. The third part of the article focused on the interaction between the two educational systems and local values, highlighting how Islamic, Christian, and traditional societies accepted the new education. The fourth part dealt with an analysis of the political situation and the government's avoidance of ethnic conflicts resulting from the adoption of a local language in education. Finally, the fifth part reviewed the colonial educational legacy and its impact on the current educational system, pointing out the challenges and disparities of the present and future opportunities